Protective effect of ginkgo proanthocyanidins against cerebral ischemia/reperfusion injury associated with its antioxidant effects - Cao, Wang-li (Neural Regen Res, 2016)
Proanthocyanidins have been shown to effectively protect ischemic neurons, but its mechanism remains poorly understood. Ginkgo proanthocyanidins (20, 40, 80 mg/kg) were intraperitoneally administered 1, 24, 48 and 72 hours before reperfusion. Results showed that ginkgo proanthocyanidins could effectively mitigate neurological disorders, shorten infarct volume, increase superoxide dismutase activity, and decrease malondialdehyde and nitric oxide contents. Simultaneously, the study on grape seed proanthocyanidins (40 mg/kg) confirmed that different sources of proanthocyanidins have a similar effect. The neurological outcomes of ginkgo proanthocyanidins were similar to that of nimodipine in the treatment of cerebral ischemia/reperfusion injury. Our results suggest that ginkgo proanthocyanidins can effectively lessen cerebral ischemia/reperfusion injury and protect ischemic brain tissue and these effects are associated with antioxidant properties.